Lattice Boundary Enhancement on Thermoelectric Behaviors of Heavily Boron‐Doped Silicon for Energy Harvesting: Electrical versus Thermal Conductivity - Shang Yu Tsai; Po‐Hsien Tseng; Chun Chi Chen; Cheng‐Ming Huang; Hung‐Wei Yen; Yi‐Sheng Chen; Kun‐Lin Lin; Ranming Niu; Yu‐Sheng Lai; Fu‐Hsiang Ko (Advanced Materials Interfaces)
Abstract Green energy collection is crucial for achieving future net‐zero carbon emissions, with energy harvesting being a key solution. Silicon, a widely used p‐type semiconductor doped with boron ions, is prevalent in modern electronics. However, the impact of lattice boundaries from ion implantation doping on thermoelectric properties remains underexplored. A heavily boron‐doped silicon layer is used to enhance thermoelectric performance. The layers, formed on silicon, exhibit epitaxial crystal structures under all doping conditions using an ion implantation system. Transmission electron microscopy and atom probe tomography reveal that boron interstitial structures create boundaries in the silicon lattice. These boundaries effectively reduce the thermal conductivity of boron‐doped silicon compared to intrinsic silicon. At 372.76 K, the best power factor of the heavily boron‐doped silicon layer is 3.05 mW/m·K2, obtained at an implant dose of 1016 cm−2. This study demonstrates the raised electrical conductivity is induced by effectively substituting silicon with boron atoms, and the reduced thermal conductivity is caused by boron interstitial‐formed boundaries in silicon. These findings highlight the potential of heavily boron‐doped silicon in improving thermoelectric materials and advancing energy‐efficient technologies.